Tingkat Literasi Pasar Modal (Studi Pada Dosen Fakultas Ekonomi UMN Al Washliyah Medan) - Ardhansyah Putra Hrp; Dwi Saraswati (Journal of Trends Economics and Accounting Research, 2023)
The purpose of this study is to find out how the capital market knowledge owned by lecturers, how to know the types of capital market investment instruments, how to know the level of capital market investment benefits, owned by lecturers how to know the level of investment risk owned by lecturers of the Faculty of Economics and how the design model for optimizing capital market literacy for lecturers Faculty of Economics UMN AL Washliyah. Abstract is a short summary of the paper to help the reader quickly ascertain the purpose of the study and match the research needs. The type of data used in this study was primary data, which was obtained directly from respondents. The total population and respondents in this study were permanent lecturers of the Faculty of Economics, totaling 60 respondents. The data analysis technique used in this study used frequency distribution. The results showed that the lecturer's understanding of Investment Knowledge in the Capital Market was still not optimal (understanding good categories). Things that are not well understood are about parties who have excess funds between the public or companies, the still mixed concept of profits obtained by investment instruments in the capital market and banking, and the form of stock investment risk in the form of not getting dividends and the possibility of bankruptcy for companies that have go public.